2008
DOI: 10.1038/nature07535
|View full text |Cite|
|
Sign up to set email alerts
|

Major gradients in putatively nitrifying and non-nitrifying Archaea in the deep North Atlantic

Abstract: Aerobic nitrification of ammonia to nitrite and nitrate is a key process in the oceanic nitrogen cycling mediated by prokaryotes. Apart from Bacteria belonging to the beta- and gamma-Proteobacteria involved in the first nitrification step, Crenarchaeota have recently been recognized as main drivers of the oxidation of ammonia to nitrite in soil as well as in the ocean, as indicated by the dominance of archaeal ammonia monooxygenase (amoA) genes over bacterial amoA. Evidence is accumulating that archaeal amoA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
239
9
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(276 citation statements)
references
References 30 publications
(9 reference statements)
21
239
9
5
Order By: Relevance
“…Normalization of read numbers by gene length resulted in a roughly equivalent copy number of amoA and 16S genes (amoA:16S ratio of B1.4), indicating that the majority of GB MGI cells have amoA and are thus capable of ammonia oxidation. These findings are consistent with those of Konstantinidis et al (2009) from 4000 m depth at station ALOHA and distinct from those of Agogué et al (2008), which found smaller amoA:16S ratios in deep Atlantic waters.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Normalization of read numbers by gene length resulted in a roughly equivalent copy number of amoA and 16S genes (amoA:16S ratio of B1.4), indicating that the majority of GB MGI cells have amoA and are thus capable of ammonia oxidation. These findings are consistent with those of Konstantinidis et al (2009) from 4000 m depth at station ALOHA and distinct from those of Agogué et al (2008), which found smaller amoA:16S ratios in deep Atlantic waters.…”
Section: Resultssupporting
confidence: 82%
“…Conflicting results leave open the question of whether individual MGI are capable of both heterotrophy and autotrophy or there are sub-groups that specialize in each. Whereas studies of cultures and surface waters indicate autotrophy, observations of a lower ratio of MGI amoA to 16S rRNA gene copies (Agogué et al, 2008) and decreasing MGI carbon fixation with depth (Varela et al, 2011) in the Atlantic suggest that deep-sea MGI are predominantly organoheterotrophic. Recent studies also show that the presence (and expression) of amoA genes does not necessarily indicate CO 2 fixation (Mubmann et al, 2011;Tourna et al, 2011).…”
Section: Species-resolved Transcriptomics Of Ammonia Oxidation Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…They occur in the ocean (Karner et al, 2001), in soils (Leininger et al, 2006) and lakes (Schleper et al, 1997), and in marine and estuarine surface sediments (Francis et al, 2005;Beman and Francis, 2006;Park et al, 2008). In the present day ocean, these Archaea are found to be among the most abundant micro-organisms (Karner et al, 2001;Agogué et al, 2008).…”
Section: Introductionmentioning
confidence: 99%